Effects of coating material of CA fertilizers on wheat yield and soil enzyme activities - MA Jun-wei; HUANG Pu-le; DING Wei-hua; CHEN Jun (浙江大学学报. 农业与生命科学版, 2002)
Whether the coating material of CA fertilizers lead to pollution of soil and crops is a question awaiting a reply. Hence, we investigated the influence on wheat growth and soil enzyme activities and on degradation of the high polymer ingredients. The results obtained were as follows. No undesirable effects on wheat growth and yield were observed; No significant difference in soil sucrase activity was between plots of soil treated by the coating material and the control plots. Soil catalase activity was, however, remarkably enhanced. The degradation rate of coating material in soils was about 3% in 4 months under 25 C indoor.